Grain boundaries and hetero-interfaces in Ti-based high temperature superconductors - Grovenor, C; Bramley, A; O'Connor, J; Eastell, C; Moore, J (Minerals, Metals and Materials Soc (TMS), 1998)
Many kinds of internal interfaces can influence the properties of bulk and thin film samples of high temperature superconductors. We have studied the growth modes of Tl(2212), Tl(2223) and Tl(1223) thin films on different substrates and buffer layers by AFM, XRD, Orientation Imaging Microscopy and cross-sectional TEM, and correlated the superconducting microwave performances with interfacial reaction characteristics and lattice defect concentrations. In addition, we have investigated the microstructure of Tl(1223) tapes by TEM, making observations on grain boundary structure and preferential alignment effects between grains and at Tl(1223)/silver interfaces. These observations have been linked to the macroscopic superconducting properties of the tapes.